2004
DOI: 10.1590/s1413-70542004000400019
|View full text |Cite
|
Sign up to set email alerts
|

Influência de solventes orgânicos na adsorção de linalol e decanal em sílica gel

Abstract: RESUMOEstudou-se a influência de solventes orgânicos (etanol, propanol e acetato de etila) na isoterma de adsorção de uma solução-modelo do óleo essencial de laranja em sílica-gel. A solução-modelo constituiu-se de compostos oxigenados (linalol e decanal) dissolvidos em d-limoneno (solvente). A influência da temperatura no processo de adsorção foi determinada para sistemas ternário (d-limoneno + linalol + decanal) à temperatura de 298,15 K. Para o composto oxigenado decanal, os solventes que mais influenciaram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The use of the hydrophilic monomers (GDMA and HEMA) in the RAMIP and RANIP syntheses resulted in a hydrophilic layer on each polymer, but with a chemical composition similar to the MIP and NIP. 21,22 All the polymers retained the OXP from the solutions at pH 7.0 more efficiently. Probably most of the radiation penetrated through it, reaching the polymeric cores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the hydrophilic monomers (GDMA and HEMA) in the RAMIP and RANIP syntheses resulted in a hydrophilic layer on each polymer, but with a chemical composition similar to the MIP and NIP. 21,22 All the polymers retained the OXP from the solutions at pH 7.0 more efficiently. Probably most of the radiation penetrated through it, reaching the polymeric cores.…”
Section: Resultsmentioning
confidence: 99%
“…By the way, chemical adsorption or chemisorption involves the interaction between the adsorbent and adsorbate, with energy almost as high as the chemical bond formation. 21,22 All the polymers retained the OXP from the solutions at pH 7.0 more efficiently. It was also observed that the adsorption equilibrium was reached in 60.0 min, according to the adsorption kinetic studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Citrus essential oils are widely used in the food, pharmaceutical, and cosmetic industries, as natural flavoring substances that enhance organoleptic sensations (taste and aroma) of several products (Cornélio et al, 2004). In the food industry alone, Citrus essential oils represent 40 % of the total essential oils employed (Ferrua et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Na Tabela 3 são mostrados alguns exemplos de faixas de linearidade, assim como de limites de detecção para metodologias desenvolvidas com a reação de Berthelot ou sua versão modificada com salicilato para quantificar amônia em diferentes amostras.Tabela 3 -Faixas de linearidade e limites de detecção determinados para a quantificação de amônia utilizando a reação de Berthelot ou sua versão modificada.A adsorção pode ser definida como um processo no qual moléculas de uma substância se acumulam em uma interface(DABROWSKI, 2001); um fenômeno que ocorre na interface de duas fases, em que uma espécie química se concentra na superfície de uma outra espécie química com conseqüente troca de calor(GUERREIRO et al, 2004) ou ainda a transferência de um ou mais constituintes de uma fase fluida para a superfície do adsorvente(CORNÉLIO et al, 2004). , conhecida como energia livre de Gibbs (∆G) (ANTONIO, 2003).Aroguz(2006), estudou os parâmetros termodinâmicos (∆G, ∆H e ∆S) no processo de remoção do pesticida azinfosmetil de solução aquosa com um biosorvente nas temperaturas (30, 40, 50 e 60)ºC.…”
unclassified